Mapping QTL for Root and Shoot Morphological Traits in a Durum Wheat × T. dicoccum Segregating Population at Seedling Stage. (6th August 2017) - Iannucci, Anna; Marone, Daniela; Russo, Maria Anna; De Vita, Pasquale; Miullo, Vito; Ferragonio, Pina; Blanco, Antonio; Gadaleta, Agata; Mastrangelo, Anna Maria
Abstract : A segregating population of 136 recombinant inbred lines derived from a cross between the durum wheat cv. "Simeto" and the T. dicoccum accession "Molise Colli" was grown in soil and evaluated for a number of shoot and root morphological traits. A total of 17 quantitative trait loci (QTL) were identified for shoot dry weight, number of culms, and plant height and for root dry weight, volume, length, surface area, and number of forks and tips, on chromosomes 1B, 2A, 3A, 4B, 5B, 6A, 6B, and 7B. LODs were 2.1 to 21.6, with percent of explained phenotypic variability between 0.07 and 52. Three QTL were mapped to chromosome 4B, one of which corresponds to the Rht-B1 locus and has a large impact on both shoot and root traits (LOD 21.6). Other QTL that have specific effects on root morphological traits were also identified. Moreover, meta-QTL analysis was performed to compare the QTL identified in the "Simeto" × "Molise Colli" segregating population with those described in previous studies in wheat, with three novel QTL defined. Due to the complexity of phenotyping for root traits, further studies will be helpful to validate these regions as targets for breeding programs for optimization of root function for field performance.